Very high gravity (VHG) ethanol fermentation from sago starch by saccharomyces cerevisiae - Nadiayatul Atikah, Bt Harun (University Malaysia Sarawak, UNIMAS., 2013)
Very high gravity (VHG) fermentation is a technology that required a fermentation of higher concentrations of substrate and, therefore, increased final ethanol concentration in the medium. The fermentation was using Hydrolysed Sago Starch (HSS) as a glucose sources and Saccharomyces cerevisiae as a microorganism to produce the ethanol. The effects of high concentration of glucose on ethanol concentration were investigated in this study. The sago starch of 100 g/l, 200 g/l and 300 g/l were used as substrate in this study, with the same concentration of glucose commercial were used as control. Fermentation was conducted at 30̊ C, pH 5.5 – 6.5 and agitation rate 0f 100 rpm which were control constantly throughout fermentation. The increase of glucose concentration had enhanced microbial growth in medium.The glucose consumption in all fermentation was not different significantly whereas the highest ethanol production, 145.06 g/l was achieved by using 300 g/l of HSS. This show that the ethanol production increase accordance with the utilization of higher HSS concentration.Therefore, the optimum HSS concentration for the highest ethanol production was 300 g/l in consideration of the highest ethanol production while consuming the same amount of electricity, time and labour as in fermentation by using 100 g/l and 200 g/l of HSS.